2004
DOI: 10.1128/aem.70.12.7288-7294.2004
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Incidence of Autochthonous Antagonistic Roseobacter spp. and Vibrionaceae Strains in a Turbot Larva ( Scophthalmus maximus ) Rearing System

Abstract: Bacteria inhibitory to fish larval pathogenic bacteria were isolated from two turbot larva rearing farms over a 1-year period. Samples were taken from the rearing site, e.g., tank walls, water, and feed for larvae, and bacteria with antagonistic activity against Vibrio anguillarum were isolated using a replica plating assay. Approximately 19,000 colonies were replica plated from marine agar plates, and 341 strains were isolated from colonies causing clearing zones in a layer of V. anguillarum. When tested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 40 publications
3
67
1
Order By: Relevance
“…However, most of them, with the possible exception of the Oceanospirillales species, could not establish stable colonizing populations in the early steps of surface community development, in contrast to the surfacecolonizing Rhodobacterales species. It has been found that certain Roseobacter clade bacteria produce antibacterial compounds when they are growing on a surface, preventing other bacteria, including ␄-Proteobacteria, from colonizing the surface and forming a biofilm (8,10,11,24,44,48). A strain was even found to invade and disperse preestablished biofilms formed by other bacteria (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of them, with the possible exception of the Oceanospirillales species, could not establish stable colonizing populations in the early steps of surface community development, in contrast to the surfacecolonizing Rhodobacterales species. It has been found that certain Roseobacter clade bacteria produce antibacterial compounds when they are growing on a surface, preventing other bacteria, including ␄-Proteobacteria, from colonizing the surface and forming a biofilm (8,10,11,24,44,48). A strain was even found to invade and disperse preestablished biofilms formed by other bacteria (45).…”
Section: Discussionmentioning
confidence: 99%
“…Once the Roseobacter clade bacterial populations reach a certain density, they may actively expel or take advantage of the other surface-attaching bacteria via quorum-sensing-regulated antibiotic production and other mechanisms (8,10,11,24,35,44,45,48,57). Quorum sensing may also be important for multispecies biofilm formation (22,35,58).…”
Section: Discussionmentioning
confidence: 99%
“…Phaeobacter were found in turbot larva rearings (Hjelm et al, 2004), cutaneous mucus of seahorses (BalcĂĄzar et al, 2010) and on cephalopods (Grigioni et al, 2000;Barbieri et al, 2001). In the Chinese Changjiang estuary, close relatives of P. gallaeciensis are among the most abundant bacterial groups (Sekiguchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some species are found as symbionts in specialized luminous organs of marine fish and invertebrates, whereas a number of other species are well-known pathogens of humans or marine animals (Thompson et al, 2004). To date, relatively few studies have shown that vibrios can produce antimicrobial substances (Hjelm et al, 2004;Long & Azam, 2001;Sugita et al, 1997). However, these vibrios were not identified at the species level.…”
mentioning
confidence: 99%